2022
DOI: 10.3390/md20030165
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Three Chitinases with Potential in Direct Conversion of Crystalline Chitin into N,N′-diacetylchitobiose

Abstract: Chitooligosaccharides (COSs) have been widely used in agriculture, medicine, cosmetics, and foods, which are commonly prepared from chitin with chitinases. So far, while most COSs are prepared from colloidal chitin, chitinases used in preparing COSs directly from natural crystalline chitin are less reported. Here, we characterize three chitinases, which were identified from the marine bacterium Pseudoalteromonas flavipulchra DSM 14401T, with an ability to degrade crystalline chitin into (GlcNAc)2 (N,N’-diacety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 94 publications
(123 reference statements)
0
18
0
Order By: Relevance
“…Actually, (GlcNAc) 2 ( N , N ’-diacetyl-chitobiose) has significant relevance to the biotechnological, pharmaceutical, cosmetic, food, and agriculture industries due to its wide range of biological activities [ 7 , 10 ]. In this sense, (GlcNAc) 2 can be used as a cosmetic ingredient due to its high solubility and as a building block for polysaccharide synthesis [ 7 , 11 ]. From an economic perspective, the market price of (GlcNAc) 2 is approximately US $2000 per g, thus representing about 10,000 times more than GlcNAc [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, (GlcNAc) 2 ( N , N ’-diacetyl-chitobiose) has significant relevance to the biotechnological, pharmaceutical, cosmetic, food, and agriculture industries due to its wide range of biological activities [ 7 , 10 ]. In this sense, (GlcNAc) 2 can be used as a cosmetic ingredient due to its high solubility and as a building block for polysaccharide synthesis [ 7 , 11 ]. From an economic perspective, the market price of (GlcNAc) 2 is approximately US $2000 per g, thus representing about 10,000 times more than GlcNAc [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant PR1 genes are polygenic; however, only some genes participate in disease resistance. A study reported that only the VvPR1b1 gene in grape plants was involved in the resistance to P. syringae pv.tabaci [ 14 ]. Bonasera et al [ 15 ] transferred PR-1a , PR-1b , and PR-1c into apple seedlings and found no disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal chitin is usually produced by processing chitin with concentrated acids to destroy the crystalline structure and enhance the approach of chitin to chitinase and lytic polysaccharide monooxygenases. Therefore, colloidal chitin is commonly applied as the substrate for chitinase to prepare COSs and GlcNAc ( Ren et al, 2022 ). Meanwhile, resources of ocean-derived chitin contain about 3% NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Marine chitinases possess higher pH and salinity tolerance than chitinases from terrestrial organisms ( Han et al, 2009 ). These chitinases exist in the marine bacteria Pseudoalteromonas flavipulchra DSM 14401 ( Ren et al, 2022 ) and the Paenibacillus strain UMBR 0002 ( Liu et al, 2020 ). Researchers have identified chitinases produced by more than 30 marine bacteria ( Xinyue et al, 2021 ), but few studies have investigated chitinase in marine fungus.…”
Section: Introductionmentioning
confidence: 99%